Anasarca as the initial symptom in a Japanese girl with Sjögren's syndrome. Issue 2 (3rd July 2017) - Ueki, Masahiro; Kobayashi, Ichiro; Tozawa, Yusuke; Konishi, Shohei; Takezaki, Shunichiro; Okamoto, Takayuki; Yamada, Masafumi; Ariga, Tadashi
Abstract: Generalised oedema, or anasarca, is a rare complication of systemic lupus erythematosus (SLE) and Sjögren's syndrome (SS) and usually results from nephrotic syndrome or protein-losing enteropathy. We report a 14-year-old girl presented with anasarca and persistent fever. Despite hypoalbuminemia, no or little protein loss was observed in her urine or stool. She was diagnosed as having SS by positive anti-SSA antibodies and ductal dilation and glandular destruction of her parotid gland on magnetic resonance sialography. Elevated levels of serum C-reactive protein, ferritin and plasma D-dimer suggested that systemic inflammation caused anasarca by both decreased production of albumin and hyperpermeability associated with vascular endothelial damage similar to systemic capillary leak syndrome. Methylprednisolone pulse therapy and low-dose intravenous cyclophosphamide therapy followed by oral prednisolone and azathioprine were effective.